Sustainable Food Self-Sufficiency Policy to Increase Food Crop Productivity - Susanti Susanti; Budiharjo Budiharjo; Dedeh Maryani; Pandji Sukmana (Program Magister Ilmu Hukum Universitas Ekasakti, 2026)
Food self-sufficiency remains an important component of Indonesia's national development agenda, especially amid growing challenges such as climate change, land conversion, and population growth. This study examines the implementation of sustainable food self-sufficiency policies and their impact on increasing the productivity of staple crops, particularly rice, corn, and soybeans. This study uses a qualitative-descriptive approach with a case study design. Data collection was conducted through in-depth interviews, policy document analysis, and field observations involving stakeholders in the district agricultural office, agricultural extension workers, and local farmers. This study aims to assess the implementation of existing sustainable food self-sufficiency policies, identify factors causing low productivity of staple crops, and formulate an effective collaboration model for policy implementation. Preliminary findings indicate that although a number of national policy instruments have been localized at the regional level, their implementation is still hampered by infrastructure limitations, a lack of human resources, and weak coordination between agencies. In addition, environmental conditions and the socio-economic limitations of the community have further exacerbated productivity levels.